2019
DOI: 10.1186/s40248-019-0185-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and outcomes of patients coming from the community with sepsis due to multidrug resistant bacteria

Abstract: Background Although previous studies showed an increasing prevalence of infections due to multi-drug resistant (MDR) bacteria in the community, specific data on sepsis are lacking. We aimed to assess prevalence, risk factors and outcomes of patients with sepsis due to MDR bacteria. Methods An observational, retrospective study was conducted on consecutive adult patients coming from the community and admitted to the Policlinico Hospital, Milan, Italy, with a diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 36 publications
3
33
4
Order By: Relevance
“…Capsoni et al in his recent study reported MDR isolates should be considered as a signi icant independent risk factor for mortality. This clearly indicates variable incidence rate of MDRPA and the need for judicious use of empirical drugs in Pseudomanas infections (Capsoni et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Capsoni et al in his recent study reported MDR isolates should be considered as a signi icant independent risk factor for mortality. This clearly indicates variable incidence rate of MDRPA and the need for judicious use of empirical drugs in Pseudomanas infections (Capsoni et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Regarding multidrug-resistant organisms, Mangioni and others [ 25 ] stressed the importance of triage in sepsis patients. Capsoni et al [ 26 ] described that ESBLs were life-threatening in sepsis patients. Our study disclosed, however, that MRSA was a significant factor in morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…A mild form with single organ system dysfunction can be managed by moderate support, while multiple organ dysfunction requires invasive therapies [23]. Although broad-spectrum antibiotics are integral in the management of sepsis, a major challenge associated with antibiotic therapy in sepsis is resistance by pathogens that adversely affects sepsis outcomes and increases mortality rates by approximately two-fold [7,25]. Globally, an estimated 214,000 deaths due to neonatal sepsis are thought to be caused by resistant pathogens [26,27].…”
Section: Introductionmentioning
confidence: 99%